Unifying theories of programming : 7th International Symposium, UTP 2019, dedicated to Tony Hoare on the occasion of his 85th birthday, Porto, Portugal, October 8, 2019, Proceedings /: 7th International Symposium, UTP 2019, dedicated to Tony Hoare on the occasion of his 85th birthday, Porto, Portugal, October 8, 2019, Proceedings. (2019) - Unknown
No abstract available